Model sodobnega umetnostnega kotalkarja - Mikeln, Špela (Šport (Ljubljana), 2023)
Artistic roller skating is a competitive sports discipline in which the competitors are using specific skating shoes, attached to a plate with small wheels and with a break in the front for movement in sports halls or outside on concrete surfaces. Skaters can compete in different disciplines separated by age, however the focus of this article is the discipline of free skating. The main feature of free skating is improved proficiency of certain technical elements which are jumps, spins, footwork sequence and cho- reographic sequence. These elements are connected into a programme while their execution has to match with the rhythm and theme of the individually chosen music. In this articale we‘ve done a thorough research of a profound model of an artistic roller skater and areas of their physical preperation. In order to achieve success, artistic roller skaters from the age category of cadets and on should strive to improve predominantly development of power, take-off power, specific endurance, specific coordination, balance and flexibility.
Keywords: aerobne sposobnosti; gibalne sposobnosti; kotalkanje; šport; telesna priprava; umetnostno kotalkanje